2022
DOI: 10.1186/s43163-022-00231-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient otoacoustic emissions with contralateral suppression findings in COVID-19 patients

Abstract: Objective The virus called SARS-CoV-2, which is known as the first epidemic of the twenty-first century, is known to affect the central and peripheral nervous system. In the literature, complaints of sudden hearing loss, tinnitus, and vertigo have been reported in the patients. The aim of this study is to objectively reveal the effect of the coronavirus disease 2019 on the efferent auditory system. Methods Twenty-three participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…In agreement, in the study of Basoz et al, (17) , both air and bone pure tone audiometry of the patient group were found significantly higher than the control group (p < 0.05). When the speech tests of the participants were examined, the SRTs of the patient group were significantly higher (p = 0.000), while a significant decrease was not obtained in the speech discrimination scores (p = 0.804).…”
Section: Discussionsupporting
confidence: 88%
“…In agreement, in the study of Basoz et al, (17) , both air and bone pure tone audiometry of the patient group were found significantly higher than the control group (p < 0.05). When the speech tests of the participants were examined, the SRTs of the patient group were significantly higher (p = 0.000), while a significant decrease was not obtained in the speech discrimination scores (p = 0.804).…”
Section: Discussionsupporting
confidence: 88%
“…Basoz et al (2022) used the ILO-292-II device for to measure suppression and presented 75 peSPL of stimulus and 60 dB SPL of broadband noise. The minimum reproducibility was 70%, whereas the stability threshold was 80 19 . Koca et al (2022) presented noise using an external audiometer with inserted earphones for the CS test.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the TEOAE results of post-COVID-19 at 3000 and 4000 Hz were lower than those of the pre-COVID-19 period. Basoz et al stated that both the emission and suppression results were lower in a study group with a history of COVID-19, especially at high frequencies 19 . In another study evaluating the efferent system in adults after COVID-19, a decrease was observed at 6 kHz according to the DPOAE results, and at all frequencies according to the contralateral suppression results in the study group 20 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations